Detect Fraud Financial Statements with Theory Fraud Diamond During the Covid-19 Pandemic - Herlambang, Yudi (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2022)
The impact of the Covid-19 pandemic shook the world economy, especially Indonesia. BPS data Compared to January 2019, there was a decline in imports of capital goods and raw materials, or year on year (yoy) basis, which affected the performance of the manufacturing industry. This research aims to detect indications of financial statement fraud in companies affected by the Covid-19 pandemic, especially manufacturing, with proxies for financial stability, nature of industry, change in auditors and change of directors. Descriptive and verification research methods with multiple linear regression analysis were processed using the EViews-12 application, an optional source of information about manufacturing organizations listed on the Indonesia Stock Exchange in 2020, a total population of 191 companies using a purposive sampling technique so that the total sample is 84 companies. The results of research on the condition of financial stability, nature of industry, change in auditors, change of directors and financial statement fraud under normal conditions. Simultaneously all the independent variables have a significant effect with the direction of a positive relationship to financial statement fraud. Partially, financial stability and nature of industry have a significant effect in the direction of a negative relationship, then change in auditors has a significant effect on a positive relationship, then change of directors has no effect on a negative relationship, all of this on financial statement fraud.